Author Correction: Fully Automatic System for Accurate Localisation and Analysis of Cephalometric Landmarks in Lateral Cephalograms - Claudia Lindner (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.